HUBUNGAN RIWAYAT HIPERTENSI DENGAN KEJADIAN PREEKLAMPSIA PADA IBU BERSALIN DI RSUD EMBUNG FATIMAH KOTA BATAM TAHUN 2017 - Sabgustina, Pirma Vicktria; Anjani, Arum Dwi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Almost 10 million expectants suffer preeclampsia and almost 76 thousand die from preeclampsia and hypertension every year. The purpose of this study is to unravel the Relationship of Hypertension Record with Preeclampsia on Labor. Analytical survey reserach design with cross sectional approach was conducted in this research. Research was completed from May-July 2017 at RSUD Embung Fatimah Batam. The population was all labor women of 108 respondents by using Total Sampling technique. The research instrument used the checklist sheet. The data analysis used was univariate and bivariate, bivariate analysis technique used was Chi-square test by using p-value significance of p-values < (Î±) 0,05. The results of the study was found expectants with hypertension record of 42 respondents (38,9%) and preeclampsia record of 45 expectant (41,7%). Chi-Square test result shows that p = 0.00 <0.05 means there is a correlation between hypertension history and preeclampsia occurrence. Suggestion for the respondents is expected to do regular check so that it can be detected early on with problems during pregnancy or labor especially signs of preeclampsia.